A science of our own : exhibitions and the rise of Australian public science - Hoffenberg, Peter H., 1960- (Science and culture in the nineteenth century., 2019)
"When the Reverend Henry Carmichael opened the Sydney Mechanics' School of Arts in 1833, he introduced a bold directive: for Australia to advance on the scale of nations, it needed to develop a science of its own. Prominent scientists in the colonies of New South Wales and Victoria answered this call by participating in popular exhibitions far and near, from London's Crystal Place in 1851 to Sydney, Melbourne, Adelaide, and Brisbane during the final decades of the nineteenth century"--